PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIISMPN 14 PADANG - Ningsih, Silvia; Zulfaneti, Zulfaneti; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACT This research bagkground by mathematics learns student result at SMPN 14 Padang still lower. This represent one of the factor that able to indicate that students domination to understanding of mathematical concept also still lower. This research type is experiment research, with research design random to subject. Population in this research is VIII class student in the year of Lesson 2013 / 2014. Intake of sample technique is random, the chosen sample class is VIII.3 class is experiment and VIII.7 class as control class. Instrument which is used in this research is final learn test in the form of essay with problem reliability 0,80. Data analyze technique that used is t test one party with MINITAB program. Pursuant to result of data analysis is obtained mean of result of learning experiment class student is 70,28, higher if compared to class control that is 59,75. The hypotesis examination use MINITAB program with t test, is obtained P-Value = 0,029 < is specified that is 0,05. So, can be concluded that understanding of mathematical concept studen applying of Teams Games Tournament (TGT) type cooperatif studying better than the understanding of mathematical concept control class student with convensional study at VIII Class SMPN 14 Padang at trust level 95% ( = 0,05).